Heterogeneity on high-resolution [alpha]s plots for carbon nanotubes—GCMC study - Terzyk, A.; Gauden, P.; Furmaniak, S.; Kowalczyk, Poitr (Royal Society of Chemistry, 2008)
We present the first study showing the influence of heterogeneityof the internal wall of carbon nanotubes on the shape of highresolution as-plots.The concept of comparative plots was first proposed byShull in 1948,1 and from that time it has been developed bydifferent authors.1 This idea inspired Lippens and deBoer1who proposed so called t-plot in 1965. Since the term monolayerwas controversial for adsorption in carbon micropores,Sing proposed the more general idea of the as-plot1 developedfurther by Lecloux and Pirard.1 Today due to experimentalpossibilities in determination of low-pressure isotherms, usuallythe high-resolution as-plot (called here HRAP) is used, asproposed by Kaneko et al.2 This method is a standard tool forcharacterisation of porosity of adsorbents. Due to progress inmolecular simulations it was possible to present the generalclassification of HRAPs and the relation between the shape(and deviations from linearity) and the mechanism of adsorptionand pore size distribution of an adsorbent. However, theclassifications of this type are usually based on the models ofideal pores, for example slits with homogeneous pore walls.